An analysis of reproductive performance in pigs based on records of performance of the boar - Baharin, K.; Beilharz, R. G. (Commonwealth Scientific and Industrial Research Organization for the Australian Agricultural Council, 1977)
The reproductive performance of 308 boars with total records of 9220 matings from a large commercial farm was analysed. The boars were purebred Large White, Landrace and from the newly synthesized M breed and were mated to purebred and crossbred sows of the same breeds. The M breed was derived from crossing between Large White and Landrace pigs with foundation females selected on the basis of their ability to produce large litters. Over half the total records were from matings with sows of parity 1 and parity 2. Overall production statistics were 78.8 per cent conception rate, an average total litter size of 9.3 pigs born per litter, 6.5 per cent stillbirths, an average litter weight (live piglets) at birth of 12.2 kg, average birth weight per piglet of 1.43 kg and average gestation length of 11 5 days. Most of the traits analysed showed significant effects due to parity of dams, with performance increasing from parity 1 to parity 6 to 8, after which the performance began to decline. There were significant heterosis effects (mainly maternal) on reproduction of the sows and survival performance of the litters resulting in an estimated improvement of 11 per cent in number of live pigs born, 12.4 per cent in total litter weight at birth and 35 per cent reduction in stillbirths. Heritability estimates were generally low for most traits except for boar conception rate which was moderate (0.29).